Efikasi Herbisida Metil Metsulfuron terhadap Pertumbuhan Gulma pada Budidaya Kelapa Sawit (Elaeis guineensis Jacq.) Tanaman Belum Menghasilkan (TBM) - Villian, Jimmy; Pujisiswanto, Hidayat; Evizal, Rusdi; Sriyani, Nanik (JURNAL AGROTROPIKA, 2024)
The oil palm plant which has the Latin name Elaeis guineensis Jacq. is one of the main plantation commodities in Indonesia. The growth of weeds on oil palm cultivation land causes competition for growth facilities and affects the growth of oil palm plants (TBM). One of the active ingredients of herbicides used to control weeds in TBM oil palm plantations is metsulfuron methyl herbicide. This study aims to determine the effective dose of 20% metsulfuron methyl herbicide in suppressing weed growth in TBM oil palm plants, to determine changes in the composition of weed species that grow after the application of metsulfuron methyl herbicide, to determine the effect of phytotoxicity on TBM oil palm plants due to herbicide application. This research was conducted in an oil palm plantation in Braja Lebah Village, Braja Selebah District, East Lampung Regency and the Laboratory of Weed Science, Faculty of Agriculture, University of Lampung from August to December 2022. This study used a Randomized Block Design (RAK) with 6 treatments 6 and 4 replications with metsulfuron methyl dose as follows 15; 20; 25; 30g/ha; mechanical weeding and control. The homogeneity of the variance of the data was tested by Barlett's test and the additivity of the data was tested by using the Tukey test and the difference in the mean treatment was tested by the Least Significant Difference (LSD) test at the 5% level. The research results show that; (1) The herbicide methyl metsulfuron 20% at a dose of 15 – 30 g/ha is effective in controlling the growth of total weeds, the dominant weeds Asystasia gangetica and Praxelis climatidea, Boreria alata, Melastoma malabathricum and Richardia brasiliensis up to 12 MSA; (2) Metsulfuron Methyl Herbicide 20% at a dose of 15 – 30 g/ha caused a change in weed composition at 4, 8, and 12 MSA; (3) The application of 20% metsulfuron methyl herbicide at a dose of 15–30 g/ha does not cause poisoning in TBM oil palm plants. Keywords : efficacy, herbicide, oil palm, metsulfuron methyl